Study Of The Potential For Floating Solar Power Plant In Situ Gede Bogor City - Bilasi, Kris Stefan; Notosudjono, Didik; Rijadi, Bloko Budi (Teknik Elektro Universitas Siliwangi, 2024)
Floating Solar Power Plant utilized in research is located in Situ Gede Bogor City. The utilization of the situ area which has a land area of . With a power plant area utilization plan of 1 Hectare the potential average solar radiation at Situ Gede is . The total energy generated is . This research uses a Interactive Microgrid as a solar power system configuration scheme. The components used are Monocrystalline solar modules with a capacity of 500 Wp totaling 4200 units, 22 inverter units with a capacity of 2458 kW, a battery unit value the total capacity is 3634,634 kW with a total of 1818 battery units, and the battery inverter capacity of 25000 W, with a total battery inverter capacity value of 8034,78 kW, which is the total use of 3 battery inverter units. The simulation results on PVSyts obtained the value of solar power plant in one year is 3148720 kWh a Performance Ratio of 84.48% and a Capacity Factor value of 17.19%. With a total initial investment cost of Rp85.033.240.352, the Payback Period is obtained in a period of 11 years with an estimated operating time of 20 years.